Epidemiology of Otitis Media with Spontaneous Perforation of the Tympanic Membrane in Young Children and Association with Bacterial Nasopharyngeal Carriage, Recurrences and Pneumococcal Vaccination in Catalonia, Spain - The Prospective HERMES Study. - Robert Cilveti; Montserrat Olmo; Josefa Pérez-Jove; Juan-José Picazo; Josep-Lluis Arimany; Emiliano Mora; Tomás M Pérez-Porcuna; Ignacio Aguilar; Aurora Alonso; Francesc Molina; María Del Amo; Cristina Mendez; et al. (PLoS ONE)
The Epidemiology of otitis media with spontaneous perforation of the tympanic membrane and associated nasopharyngeal carriage of bacterial otopathogens was analysed in a county in Catalonia (Spain) with pneumococcal conjugate vaccines (PCVs) not included in the immunization programme at study time. A prospective, multicentre study was performed in 10 primary care centres and 2 hospitals (June 2011-June 2014), including all otherwise healthy children ≥2 months ≤8 years with otitis media presenting spontaneous tympanic perforation within 48h. Up to 521 otitis episodes in 487 children were included, showing by culture/PCR in middle ear fluid (MEF): Haemophilus influenzae [24.2%], both Streptococcus pneumoniae and H. influenzae [24.0%], S. pneumoniae [15.9%], Streptococcus pyogenes [13.6%], and Staphylococcus aureus [6.7%]. Culture-negative/PCR-positive otitis accounted for 31.3% (S. pneumoniae), 30.2% (H. influenzae) and 89.6% (mixed S. pneumoniae/H. influenzae infections). Overall, incidence decreased over the 3-year study period, with significant decreases in otitis by S. pneumoniae and by H. influenzae, but no decreases for mixed S. pneumoniae/H. influenzae infections. Concordance between species in nasopharynx and MEF was found in 58.3% of cases, with maximal rates for S. pyogenes (71.8%), and with identical pneumococcal serotype in 40.5% of cases. Most patients (66.6%) had past episodes. PCV13 serotypes were significantly more frequent in first episodes, in otitis by S. pneumoniae as single agent, and among MEF than nasopharyngeal isolates. All non-PCV13 serotypes separately accounted for <5% in MEF. Up to 73.9% children had received ≥1 dose of PCV, with lower carriage of PCV13 serotypes than among non-vaccinated children. Pooling pneumococcal isolates from MEF and nasopharynx, 30% were multidrug resistant, primarily belonging to serotypes 19A [29.8%], 24A [14.3%], 19F [8.3%] and 15A [6.0%]. Our results suggest that increasing PCV13 vaccination would further reduce transmission of PCV13 serotypes with special benefits for youngest children (with none or uncompleted vaccine schedules), preventing first otitis episodes and subsequent recurrences.